Modelação e controlo de um conversor CC/CC bidireccional em corrente operando em modo desacoplado - Diogo Filipe Saraiva Pereira Rodrigues (2020)
Bidirectional converters are of increasing interest since they allow for controlling of the power flow between two connections. Nowadays, the growing investment in sectors such as renewable energies or electric cars, together with a strong development of the associated technologies, contributed significantly to a greater impact of this type of converters, in the panorama of electronics. Generally working in parallel with a main system, its main function is to manage the direction of energy flow between a storage system and a load. In the case of energy production from renewable sources, due to its natural uncertainty, the possibility of excess energy storage or, on the other hand, the use of energy stored in batteries (for example) in order to aid in situations of lower production are two clear examples of the large utility of these converters. Traditionally the power management in a bidirectional converter is performed by imposing a phase angle difference between control signals, maintaining a fixed duty-cycle of 50 %. For the work to be carried out during this dissertation, the main objective will be to implement a control on both the phase-shift as well as the duty-cycle, drawing the appropriate conclusions from the results obtained. Thus, it is intended to conclude on the usefulness of the added degree of freedom of control, based on the possible advantages and disadvantages.